1979
DOI: 10.1097/00006123-197907010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral interhemispheric subdural hematomas

Abstract: Interhemispheric subdural hematomas are rare. Bilateral interhemispheric subdural hematomas in a patient with a ventriculoperitoneal shunt for hydrocephalus were diagnosed by computerized tomographic (CT) scan after mild head trauma. The value of CT scanning, the clinical presentation and treatment, and a review of the literature are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
1
7
0
3
Order By: Relevance
“…These clinicians suggest that prompt surgery via a craniotomy is the only way to deal with this condition safely. 8,12,13,16) However, some patients with an ISH have been managed successfully with conservative measures in the acute phase. 2,5,10,14) Although there is no consensus on the ideal management of these hematomas, a flexible treatment plan should be developed.…”
Section: Discussionmentioning
confidence: 99%
“…These clinicians suggest that prompt surgery via a craniotomy is the only way to deal with this condition safely. 8,12,13,16) However, some patients with an ISH have been managed successfully with conservative measures in the acute phase. 2,5,10,14) Although there is no consensus on the ideal management of these hematomas, a flexible treatment plan should be developed.…”
Section: Discussionmentioning
confidence: 99%
“…ISH is usually caused by traumatic laceration of bridging veins between the parieto-occipital cortex and the superior sagittal sinus [1, 2, 5, 9 ± 11,14,17,18, 21, 24]. It has also been described in association with anticoagulant therapy [13,19,20,24,26], shunted hydrocephalus [15], or following aneurysm rupture [8]. In addition, other authors [19,20] found ISH to be a frequent complication in the abused child with whiplash injury of the head.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, ISH is confined to one side of the falx because firm adherence of subarachnoidal trabeculations between the brain and the parasagittal dura precludes further dissemination of the bleeding [11]. Some patients with ISH have bilateral hematomas [15], or associated convexity subdural hematomas; these lesions are often related to severe head trauma causing bleeding from separate sources [10,18,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations